Comparative assessment of insecticide resistance phenotypes in two major malaria vectors, Anopheles funestus and Anopheles arabiensis in south-eastern Tanzania - Polius G. Pinda; Claudia Eichenberger; Halfan S. Ngowo; Dickson S. Msaky; Said Abbasi; Japhet Kihonda; Hamis Bwanaly; Fredros O. Okumu (Malaria Journal, 2020)
Abstract Background Long-lasting insecticide-treated nets (LLINs) and indoor residual spraying (IRS) have greatly reduced malaria transmission in sub-Saharan Africa, but are threatened by insecticide resistance. In south-eastern Tanzania, pyrethroid-resistant Anopheles funestus are now implicated in > 80% of malaria infections, even in villages where the species occurs at lower densities than the other vector, Anopheles arabiensis. This study compared the insecticide resistance phenotypes between the two malaria vectors in an area where pyrethroid-LLINs are widely used. Methods The study used the World Health Organization (WHO) assays with 1×, 5× and 10× insecticide doses to assess levels of resistance, followed by synergist bioassays to understand possible mechanisms of the observed resistance phenotypes. The tests involved adult mosquitoes collected from three villages across two districts in south-eastern Tanzania and included four insecticide classes. Findings At baseline doses (1×), both species were resistant to the two candidate pyrethroids (permethrin and deltamethrin), but susceptible to the organophosphate (pirimiphos-methyl). Anopheles funestus, but not An. arabiensis was also resistant to the carbamate (bendiocarb). Both species were resistant to DDT in all villages except in one village where An. arabiensis was susceptible. Anopheles funestus showed strong resistance to pyrethroids, surviving the 5× and 10× doses, while An. arabiensis reverted to susceptibility at the 5× dose. Pre-exposure to the synergist, piperonyl butoxide (PBO), enhanced the potency of the pyrethroids against both species and resulted in full susceptibility of An. arabiensis (> 98% mortality). However, for An. funestus from two villages, permethrin-associated mortalities after pre-exposure to PBO only exceeded 90% but not 98%. Conclusions In south-eastern Tanzania, where An. funestus dominates malaria transmission, the species also has much stronger resistance to pyrethroids than its counterpart, An. arabiensis, and can ...